Analisis Sistem Paylater terhadap Perilaku Impulse Buying Mahasiswa pada Era Digital Menurut Perspektif Islam - Wibowo, Salsabila Natasya; Hendri Hermawan Adinugraha (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
The study's goal is to examine the influence of paylater payment systems on student impulsive purchase behavior in the digital era, with a particular emphasis on the Islamic viewpoint. Increased usage of technology and electronic payment methods, such as paylaters, has sped up online purchasing transactions, which can influence customer behavior, especially impulse purchases. The study collects data from students who utilize the paylater system to perform online retail transactions using qualitative research approaches. The respondents of this research are students of UIN K.H. Abdurrahman Wahid Pekalongan. Furthermore, the study was conducted in accordance with Islamic economic principles, which promote fair, honest, and responsible transactions. According to the findings of the study, the usage of paylater systems can enhance student impulsive purchase behavior. Transactional simplicity and enticing discount offers might lead to hasty purchase decisions. However, it was discovered that several actions in the paylater system may be inconsistent with Islamic economic ethical standards. This study provides in-depth insight into how paylater payment systems impact student spending behavior and serves as a foundation for developing policy recommendations to encourage the establishment of payment systems based on Islamic principles. In the context of an ever-expanding digital economy, it is critical to encourage responsible consumerism and moral values.